2012
DOI: 10.2220/biomedres.33.329
|View full text |Cite
|
Sign up to set email alerts
|

Zinc deficiency induces dysregulation of cytokine productions in an experimental colitis of rats

Abstract: Dextran sulfate sodium (DSS)-induced colitis is an experimental model of ulcerative colitis, although the precise mechanism has not yet been elucidated. We investigate whether Zn deficiency affects the pathogenesis of colitis induced by DSS with a focus on immune responses. Male WKAH/Hkm Slc rats were fed either a Zn-adequate (ZA, 30 mg Zn/kg diet) as a control or Zndeficient (ZD, 5 mg Zn/kg diet) diet for 21 days and then treated with 2% DSS via deionized drinking water for 7 days. The disease activity index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 25 publications
2
20
0
Order By: Relevance
“…Previous studies using Se‐deficient diets (<0.01 mg/kg) showed that a time period of 12 weeks was required before Se deficiency resulted in any worsening in the colons of DSS‐induced colitis in mice . In contrast, rats fed a zinc‐deficient diet (5 mg/kg) for 3 weeks showed exacerbation of DSS‐induced colitis . In the present study, dietary Mn deficiency worsened the severity of experimental colitis and promoted IBD development in mice after feeding a low Mn diet for only 2 weeks, and the DSS treatment often led to death of the Mn‐deficient animals (Figure ).…”
Section: Resultssupporting
confidence: 39%
See 1 more Smart Citation
“…Previous studies using Se‐deficient diets (<0.01 mg/kg) showed that a time period of 12 weeks was required before Se deficiency resulted in any worsening in the colons of DSS‐induced colitis in mice . In contrast, rats fed a zinc‐deficient diet (5 mg/kg) for 3 weeks showed exacerbation of DSS‐induced colitis . In the present study, dietary Mn deficiency worsened the severity of experimental colitis and promoted IBD development in mice after feeding a low Mn diet for only 2 weeks, and the DSS treatment often led to death of the Mn‐deficient animals (Figure ).…”
Section: Resultssupporting
confidence: 39%
“…29 In contrast, rats fed a zinc-deficient diet (5 mg/kg) for 3 weeks showed exacerbation of DSS-induced colitis. 30 In the present study, dietary Mn deficiency worsened the severity of experimental colitis and promoted IBD development in mice after feeding a low Mn diet for only 2 weeks, and the DSS treatment often led to death of the Mn-deficient animals ( Figure 2). Our data underscore the crucial role of dietary Mn in maintaining intestinal mucosal homeostasis and suppressing IBD.…”
Section: Discussionmentioning
confidence: 45%
“…However, its expression and activity has not been investigated in IBD patients or in experimental models. Recently, Suwendi et al (140) showed that in DSS colitis in rats, serum zinc level was reduced regardless of dietary Zn concentration. Moreover, rats on a zinc-deficient diet showed exacerbated symptoms of colitis with increased TNFa production (140).…”
Section: Other Micronutrientsmentioning
confidence: 99%
“…Recently, Suwendi et al (140) showed that in DSS colitis in rats, serum zinc level was reduced regardless of dietary Zn concentration. Moreover, rats on a zinc-deficient diet showed exacerbated symptoms of colitis with increased TNFa production (140). Current knowledge, however limited, suggests that plasma Zn levels should be measured in IBD patients and used as a guide for supplementation with zinc sulfate.…”
Section: Other Micronutrientsmentioning
confidence: 99%
“…In animal models, zinc deficiency exacerbates colitis and potentiates production of pro-inflammatory cytokines, including tumor necrosis factor α (TNFα) (7, 8). Furthermore, previous work indicates that a low zinc diet in healthy volunteers results in a decrease in the TH1 cytokines, IFN-γ and IL-2, as well as diminished lytic activity of natural killer cells (2).…”
Section: Introductionmentioning
confidence: 99%